2023
DOI: 10.1021/acs.analchem.2c03522
|View full text |Cite
|
Sign up to set email alerts
|

Composite Multidimensional Ion Mobility-Mass Spectrometry for Improved Differentiation of Stereochemical Modifications

Abstract: Stereochemical modifications (SCMs), mostly present in the form of D-amino acid substitution, have been increasingly identified from a wide range of neuropeptides and disease-associated biomarker proteins. Traditional mass spectrometry-based SCM identification has been effectively enhanced with technological and strategic advancements in ion mobility spectrometry. With the additional separation provided by ion mobility, SCM-induced structural changes can be probed both in theory and in practice, although the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…To understand the underlying molecular mechanisms behind the altered cytotoxicity induced by D-epimerization, we aimed to rstly characterize the structural impacts of chiral inversion of Ab42. Our previously reported md-IM-MS strategy 34,41 was the clear method-of-choice, given its ability to rapidly discriminating the subtle structural differences of Ab42 stereoisomers. Expansion of this method for the analysis of full-length Ab42 requires overcoming two pressing obstacles: (1) the propensity of Ab42 to form aggregates in solution, crippling electrospray signal stability during IM-MS analysis; (2) the inadequate collision cross-section (CCS) resolution of IM-MS for Ab42 stereoisomers when using a single IM regime.…”
Section: Molecular Mechanism For Structure-activity Relationship Of A...mentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the underlying molecular mechanisms behind the altered cytotoxicity induced by D-epimerization, we aimed to rstly characterize the structural impacts of chiral inversion of Ab42. Our previously reported md-IM-MS strategy 34,41 was the clear method-of-choice, given its ability to rapidly discriminating the subtle structural differences of Ab42 stereoisomers. Expansion of this method for the analysis of full-length Ab42 requires overcoming two pressing obstacles: (1) the propensity of Ab42 to form aggregates in solution, crippling electrospray signal stability during IM-MS analysis; (2) the inadequate collision cross-section (CCS) resolution of IM-MS for Ab42 stereoisomers when using a single IM regime.…”
Section: Molecular Mechanism For Structure-activity Relationship Of A...mentioning
confidence: 99%
“…13,[31][32][33][34][35][36][37] IM-MS offers high analytical speed, low sample consumption and the ability to resolve small structural differences in peptide analytes, driven by recent technological advancements in IM-MS. [34][35][36][37][38][39] While molecular dynamics (MD) simulations have been combined with IM-MS to reveal the structural consequences of D-epimerization within small neuropeptides, 40 Li et al has recently reported a multi-dimensional IM-MS (md-IM-MS)-based structural analysis strategy, based on the metal-bound chiral amplication and oligomer-resolved data integration method, to facilitate the study of the chiral effects on monomer structure, oligomeric propensity and receptor binding for Ab fragments. 34,41 However, results from truncated Ab (e.g. Ab Nterminus and core region fragments) cannot be reliably extrapolated to predict those for the full length bioactive Ab forms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu, Tang et al reported the use of oligosaccharides as chiral selectors for amino acids in trapped ion mobility, with improved separation in the presence of metal ions . Also relying on ion mobility, Zheng, Li et al reported a multidimensional workflow for structural interrogation of peptides containing chiral amino acids …”
Section: Instrumentationmentioning
confidence: 99%
“…18 Also relying on ion mobility, Zheng, Li et al reported a multidimensional workflow for structural interrogation of peptides containing chiral amino acids. 19 Ionization is an essential yet imperfect step to transfer samples into the gas phase for MS, and has been a popular area of fundamental studies for technological improvements. Gong, Fang, Pan et al studied the reactions in ESI microdroplets and discovered that ammonium bicarbonate could be the media for a microenvironment with CO 2 for reactions and the liquid−gas interface helps to increase the ratio of conversion for amines.…”
mentioning
confidence: 99%